2005
DOI: 10.1073/pnas.0503891102
|View full text |Cite
|
Sign up to set email alerts
|

Sequential phosphorylation of CCAAT enhancer-binding protein β by MAPK and glycogen synthase kinase 3β is required for adipogenesis

Abstract: CCAAT enhancer-binding protein (C͞EBP)␤, C͞EBP␣, and peroxisome proliferator activated receptor (PPAR)␥ act in a cascade where C͞EBP␤ activates expression of C͞EBP␣ and PPAR␥, which then function as pleiotropic activators of genes that produce the adipocyte phenotype. When growth-arrested 3T3-L1 preadipocytes are induced to differentiate, C͞EBP␤ is rapidly expressed but still lacks DNA-binding activity. After a long (14-hour) lag, glycogen synthase kinase 3␤ enters the nucleus, which correlates with hyperphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
296
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 303 publications
(312 citation statements)
references
References 31 publications
12
296
1
1
Order By: Relevance
“…We recently showed that C/EBP␤ must undergo sequential phosphorylation to acquire DNA binding ability (6). Immediately after the expression of C/EBP␤, a ''priming'' phosphorylation occurs on Thr 188 catalyzed by MAP kinase, which is required but is insufficient for acquisition of DNA binding activity.…”
Section: Ifferentiation Of Growth-arrested 3t3-l1 Preadipocytes Intomentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that C/EBP␤ must undergo sequential phosphorylation to acquire DNA binding ability (6). Immediately after the expression of C/EBP␤, a ''priming'' phosphorylation occurs on Thr 188 catalyzed by MAP kinase, which is required but is insufficient for acquisition of DNA binding activity.…”
Section: Ifferentiation Of Growth-arrested 3t3-l1 Preadipocytes Intomentioning
confidence: 99%
“…C/EBP␤ activates the expression of the genes for two pleiotropic transcription factors, C/EBP␣ and PPAR␥ (4,5), which in turn activate the expression of numerous adipogenic genes. Although maximal expression of C/EBP␤ occurs rapidly (within 2-4 h) on induction of differentiation and remains at this level over the next 48 h, the acquisition of DNA binding activity by C/EBP␤ required for the expression of C/EBP␣ and PPAR␥ only occurs after a long lag period of Ϸ12-14 h (1,2,6). At the end of the lag period, growth-arrested preadipocytes synchronously enter the cell cycle and undergo several rounds of mitotic clonal expansion (2, 3), a process required for subsequent differentiation.…”
Section: Ifferentiation Of Growth-arrested 3t3-l1 Preadipocytes Intomentioning
confidence: 99%
“…7 Upon hormonal stimulation, cells begin to express C/EBPb; this protein is then serially phosphorylated by mitogen-activated protein kinase and glycogen synthase kinase b, resulting in active C/EBPb with full DNA-binding capacity. 14 Activation of C/EBPb is clearly associated with MCE, as cells without C/EBPb cannot complete clonal expansion. 15 Those studies revealed a role of MCE in adipogenesis, and they explain why C/EBPb is needed for entering the terminal differentiation process.…”
mentioning
confidence: 99%
“…MAPK/ERK itself is rapidly (Յ1 h) phosphorylated/activated after induction of differentiation (Fig. 1B) (3). Although phosphorylation of C/EBP␤ on Thr 188 persists at a high level for Ͼ24 h ( Fig.…”
mentioning
confidence: 99%
“…Blocking these steps disrupts MCE and progression of the differentiation program. The synchrony by which 3T3-L1 preadipocytes proceed through MCE has been invaluable in delineating the sequence of events that occur early in the adipocyte differentiation program (2,3).…”
mentioning
confidence: 99%